Design and Optimization of an Injectable Biomaterial for Vocal Fold Augmentation. - Friedman, Rosario. (2017)
Abstract: The vocal cords, located in the larynx, are used to create sound. When tissues in the vocal fold are damaged, the associated muscles become atrophied, or other problems arise in the larynx, and it often becomes difficult or impossible to speak. There are many forms vocal fold damage can take, such as nerve damage, muscle atrophy, or superficial scarring from cancer removal, and many treatment options are available, however there is no ideal solution for loss of voice as treatments administered differ depending on the underlying pathology. One of the most commonly used treatments, known as vocal fold augmentation injection, involves injecting a supportive material behind the vocal cords to push them toward the center of the larynx, decreasing the size of the gap between the cords in order to create sound, and making it easier to talk. While this treatment is preferred over more invasive options like laryngeal framework surgery, an augmentation material does not currently exist that meets all of the needs of this application: a long lasting, safe material that matches the viscoelasticity of the vocal fold, is easy to inject, is available off-the-shelf and augments the vocal fold sufficiently. A silk-based biomaterial solution is proposed in this thesis research, and various silk formats investigated for use in vocal fold augmentation injections. Materials are evaluated and down-selected based on rheological properties, degradation time, and in vivo safety, as well as ease of delivery and preparation that must be performed by surgeon administering the treatment.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Gary Leisk.; Committee: Luisa Chiesa, and Thomas Carroll.; Keywords: Mechanical engineering, and Biomedical engineering.